Pengaruh Obyek Wisata Setigi Dan Jumlah Kunjungan Wisatawan Terhadap Pendapatan Ekonomi Masyarakat Desa Sekapuk - Maulal Waro, Atiya; syaiful, Syaiful (GEMA EKONOMI, 2023)
The purpose of this study was to determine the effect of tourist objects and tourits visits on the economic income of the people of Sekapuk Village, Ujungpangkah District, Gresik Regency. This research was conducted at Sekapuk Ujungpangkah Gresik Selo Tirto Giri (Setigi) tourism. The data collection technique in this study was in the form of primary data by distributing quistionnaries to the surrounding community as respondents. The method used in this research is to use simple liniar analysis. The result of the data analysis show that the setigi tourism object variable has a significant effect while the tourist visits variable has no significant effect on the income of the setigi tourism economy community. This is because the number of tourist visits to tourist attractions in Setigi has not maximized the economic income of local community.